Ďábel ve folkloru - Šalanda, Bohuslav (Univerzita Pardubice, 2002)
This paper studies the devil as a demonologically important figure, focusing mainly on the formation of this figure within a European cultural context. In the creation of this demonic figure, several influences were mingled, for example, the Iranian concept of dualism, in which the noble lord Ahur Mazda stood against Ahriman. The impact of this concept is traceable in the so-called dualistic tales of creation where two opposite creative principles - God and the devil - take part. The Scandinavian, as well as Middle Eastern oral traditions concerning uncivilized giants should not be overlooked either. We can also identify it in the transformations of totemic images, especially in cases of contracts, agreements, and contests related to totemic animals and, later on, giants and devils. The figure of the devil is the result of complex transformations and mutual influences from many ideological substrata, the apocryphal tradition being one of them. This paper also takes into consideration genre differetiation in narratives about the devil. The genre of the fairytale, for example, does not present the devil as a dangerous creature. On the contrary, the devil in fairytales can be cheated, bluffed, proved stupid. His dangerousness is decreased through ridicule. Devil figures in legends are presented in much the same way as in Christianity, even though they were not originally fallen angels, but demons representing natural forces, as well as personifications of underground aspects of natural phenomena. This paper also mentions the role of medieval exempla in the formation of warning stories about the devil. Most legends about a contract with the devil have their roots in this medieval stratum as well, and the paper discusses the medieval scholar Faust's agreement with the devil in this broader context. Attention is also paid to witch-hunts, and legends involving the Templars and Freemasons. The devil became a comic figure as early as the 15th and 16th centuries and was introduced into farces. Folklore adopted the figure of the stupid devil to ar greater degree than poetry did. It presented him as a personification of the helplessness of devil and, by doing so, it illustrated a generally accepted idea of the victory of good over evil.
Keywords: Folklor; ďábel; legendy; pověsti; pohádky